Pengaruh Pestisida Nabati Ekstrak Daun Kenikir (Cosmos Caudatus) terhadap Mortalitas Ulat Grayak (Spodoptera Litura) pada Daun Bawang (Allium Fistulosum) - Ria Dwi Jayati; Fitria Lestari; Reni Betharia (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2020)
This study aims to determine the effect of kenikir leaf extract (Cosmos caudatus) on the mortality of Grayak Caterpillars (Spodoptera litura). This type of research is a laboratory experiment, with the design used is a Completely Randomized Design (CRD) consisting of five treatments and five replications. The treatments were P0 + as a control, P1 with a concentration of 25%, P2 with a concentration of 50%, P3 with a concentration of 75%, and P4 with a concentration of 100%. Data analysis techniques with steps: normality test, homogeneity test and one way anova test. Research Results, based on the One Way Anava calculation, it was obtained that Fcount = 11.40 with Ftable = 4.43. then it can be stated that the value of Fcount> F table then H0 is rejected and H1 is accepted. In the BNJ (Honest Significant Difference) test, the significance level of 1% of the effect of kenikir leaf extract on treatment A 25% (P1) was not significantly different from the concentration of 50% (P2) and 75% (P3), and at treatment D 100% (P4 ) is not significantly different from ACD, the treatment E (P0 +) is very significantly different from ABDE. Conclusion, there is a very significant effect of kenikir leaf extract (Cosmos caudatus) on mortality of armyworm caterpillar (Spodoptera litura), the higher the concentration of insecticide given, the higher mortality of armyworm caterpillar.